A Review on Machining Technology and Cutting Edge Design Methods of Spiral Bevel Gears - Fang, Zeyu; Wei, Qinglei; Wang, Hao (International Journal of Mechanical and Electrical Engineering, 2025)
Spiral bevel gears are critical high-precision transmission components widely used in demanding fields such as automotive and aerospace. Their performance is fundamentally determined by advanced machining technology and the precision design of cutting tools. This paper provides a comprehensive review of the historical evolution, current status, and future trends in spiral bevel gear manufacturing. It systematically outlines the development trajectory of machining technology, from early mechanical machines to modern fully computer numerical control (CNC) systems, exemplified by Gleason's Phoenix series, and highlights China's progress in achieving technological independence. The review then focuses on the design of cutting tool edges, a key factor influencing tooth surface quality. It analyzes research on edge geometry—from traditional straight edges to advanced curved profiles—aimed at optimizing contact patterns and reducing transmission error. The analysis reveals that while significant advancements have been made, mainstream designs often simplify edge geometry. Consequently, the future direction points toward deeper integration of intelligent, closed-loop manufacturing systems and a shift in tool design philosophy: from passive "form-following" to active "form-creating." This entails designing complex edge geometries based on conjugate surface principles and multi-physics simulations, performed in synergy with optimized process parameters and machine tool dynamics. The integration of digital twins, artificial intelligence, and additive-subtractive hybrid manufacturing is identified as the pathway to achieving next-generation gears with superior performance, precision, and reliability.